Management of outpatient with totally implantable venous access Ports during the COVID-19 epidemic. Issue 7 (19th February 2021) - Yan, Weipeng; Zhang, Chaoya; Luo, Chenggang; Li, Zilin
Abstract : Abstract: The purpose of this study was to explore the management experience of outpatient with totally implantable central venous access Ports (TIVAPs, Ports) during the epidemic, including whether the extension of the irrigation interval will affect the incidence of catheter occlusion, the reasons for the port removal rate, and the corresponding protective treatment strategies during the COVID-19 epidemic. We retrospectively analyzed the Ports evaluation and flushing procedure data between February 3, 2020 and April 3, 2020; the cases were divided into the normal group and delayed group according to the critical point of the maintenance interval of 28 days (4 weeks). We compared the incidence of catheter obstruction between the 2 groups, analyzed the causes of catheter removal events in the 2 groups, and proposed corresponding protective treatment recommendations. During the period, 329 cases were included in the study. There was no significant difference in the incidence of catheter obstruction between the 2 groups. There were 15 patients with catheter removal, 8 cases of infection, 5 cases of catheter obstruction, and 1 case of an ectopic catheter, as well as 1 case of an overturned port. During the epidemic, no hospital infections related to the Ports flushing procedure occurred. The interval of Ports flushing procedures for patients without clinical symptoms can be appropriately extended during the COVID-19 epidemic. However, once the local infection symptoms or other sources of discomfort appear, Ports assessment needs to be performed as soon as possible. Take enhanced protected and isolation measures did not increase cross-infection during outpatient's flushing procedure at non-COVID-19-designated diagnosis and treatment hospitals.